Human Cytomegalovirus Induced Aberrant Expression of Non-coding RNAs - Yu, Zhongjie; Wang, Jing; Nan, Fulong; Shi, Wenyi; Zhang, Xianjuan; Jiang, Shasha; Wang, Bin (Frontiers in Microbiology, 2022)
Human cytomegalovirus (HCMV) is a β-herpesvirus whose genome consists of double stranded linear DNA. HCMV genome can generate non-coding RNAs (ncRNAs) through transcription in its host cells. Besides that, HCMV infection also changes the ncRNAs expression profile of the host cells. ncRNAs play a key role in maintaining the normal physiological activity of cells, and the disorder of ncRNAs expression has numerous adverse effects on cells. However, until now, the relationship between ncRNAs and HCMV-induced adverse effects are not summarized in detail. This review aims to give a systematic summary of the role of HCMV infection in ncRNAs expression while providing insights into the molecular mechanism of unnormal cellular events caused by ncRNAs disorder. ncRNAs disorder induced by HCMV infection is highly associated with cell proliferation, apoptosis, tumorigenesis, and immune regulation, as well as the development of cardiovascular diseases, and the potential role of biomarker. We summarize the studies on HCMV associated ncRNAs disorder and suggest innovative strategies for eliminating the adverse effects caused by HCMV infection.